The Use of a Wearable Camera Improves Memories for Recent Significant Events in Patients with Alzheimer's Disease - Hodges, Steve; Watson, Peter; Kapur, Narinder; Woodberry, Ken; Woodberry, Emma (Memory, 2007)
Despite the severe impairment of recent episodic memories in Alzheimer’s disease, there have been few attempts to rehabilitate these deficits. In a follow-up study to previously published papers, we used a novel external memory aid to promote recall of episodic memories in patients with Alzheimer’s disease (AD). SenseCam, a small wearable camera, was worn to record significant events in the lives of six AD patients. Every two days for two weeks, each patient’s memory for the an event was assessed, followed by a systematic review of the SenseCam images. After two weeks, the image reviewss were removed stopped and longer-term recall was tested one and three months later. A written diary control condition followed the same procedure. Across 40 events the SenseCam review method resulted in significantly more details of an event being recalled over two weeks than the written diary method in five out of the six patients. At one and three months post event, three patients recalled significantly more details of events in the SenseCam condition while the other patients showed no significant difference. Viewing SenseCam images of personally experienced events may significantly improve autobiographical memory in patients with even moderate AD.